Triviality and Seriousness in Oscar Wilde's Play 'The Importance of Being Earnest' (Universitas Islam Negeri Sunan Ampel Surabaya, 2022)
This paper aims to elaborate triviality and seriousness portrayed in Oscar Wilde’s The Importance of Being Earnest (1898). The play was considered Wilde’s masterpiece, and it highlights the life in the Victorian era. The play portrays the marriage life also the importance of wealth, land, and beauty. This paper employs textual and historical approaches. The findings revealed that the play exemplifies triviality by treating serious things like trivial objects and vice versa. Marriage was seen as insignificant by the male characters in the play. Lane saw it as the reason for the champagne downgrading and a bargaining part for Algernon and Jack to have their goals. Meanwhile, unimportant thing like the name was treated as if it was life matter. Cecily and Gwendolen saw a particular name as the main requirement for choosing a husband. This paper concludes that Oscar Wilde made use of such a technique on purpose to make fun of the Victorian way of life.